Gonadal Steroid Hormones Maintain the Stress-Induced Acetylcholine Release in the Hippocampus: Simultaneous Measurements of the Extracellular Acetylcholine and Serum Corticosterone Levels in the Same Subjects - Mitsushima, Dai; Takase, Kenkichi; Funabashi, Toshiya; Kimura, Fukuko (Endocrinology (Philadelphia), 2008)
To examine the role of gonadal steroid hormones in the stress responses of acetylcholine (ACh) levels in the hippocampus and serum corticosterone levels, we observed these parameters simultaneously in intact, gonadectomized, or gonadectomized steroid-primed rats. In both sexes of rats, neither gonadectomy nor the replacement of gonadal steroid hormone affected the baseline levels of ACh. However, gonadectomy severely attenuated the stress response of ACh, whereas the replacement of corresponding gonadal hormone successfully restored the response to intact levels. The gonadal hormones affected the serum corticosterone levels in a different manner; the testosterone replacement in orchidectomized rats suppressed the baseline and the stress response of corticosterone levels, whereas the 17β-estradiol replacement in ovariectomized rats increased the levels. We further found that letrozole or flutamide administration in intact male rats attenuated the stress response of ACh. In addition, flutamide treatment increased the baseline levels of corticosterone, whereas letrozole treatment attenuated the stress response of corticosterone. Moreover, we found a low positive correlation between the ACh levels and corticosterone levels, depending on the presence of gonadal steroid hormone. We conclude that: 1) gonadal steroid hormones maintain the stress response of ACh levels in the hippocampus, 2) the gonadal steroid hormone independently regulates the stress response of ACh in the hippocampus and serum corticosterone, and 3) the sex-specific action of gonadal hormone on the cholinergic stress response may suggest a neonatal sexual differentiation of the septohippocampal cholinergic system in rats.